2022
DOI: 10.3390/cancers14040997
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cells in Breast Cancer Patients: A Balancing Act between Stemness, EMT Features and DNA Damage Responses

Abstract: Circulating tumor cells (CTCs) traverse vessels to travel from the primary tumor to distant organs where they adhere, transmigrate, and seed metastases. To cope with these challenges, CTCs have reached maximal flexibility to change their differentiation status, morphology, migratory capacity, and their responses to genotoxic stress caused by metabolic changes, hormones, the inflammatory environment, or cytostatic treatment. A significant percentage of breast cancer cells are defective in homologous recombinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 241 publications
(359 reference statements)
0
2
0
Order By: Relevance
“…The DNA damage response is a complex series of mechanisms responsible for maintaining the stability and integrity of the genome by detecting and eliminating abnormal sequences and structures within chromosomes 48 . Tumor cells develop mechanisms that enable them to evade certain therapeutic strategies by co-opting the MMR 49 and HRR 50 mechanisms, endowing these tumor cells with stem-like self-maintenance abilities 51 . As such, the associations between PSME2 expression levels and MMR-associated genes, HRR signatures, and stemness were next evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…The DNA damage response is a complex series of mechanisms responsible for maintaining the stability and integrity of the genome by detecting and eliminating abnormal sequences and structures within chromosomes 48 . Tumor cells develop mechanisms that enable them to evade certain therapeutic strategies by co-opting the MMR 49 and HRR 50 mechanisms, endowing these tumor cells with stem-like self-maintenance abilities 51 . As such, the associations between PSME2 expression levels and MMR-associated genes, HRR signatures, and stemness were next evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…41 Furthermore, studies have suggested that DSB repair may be involved in fibrosis. 42,43 EMTassociated transcription factors may also regulate DSB repair, [44][45][46][47][48] indicating that there may be crosstalk between DSB repair and EMT, and the role of DNA-PKcs-mediated regulation of DSB repair and senescence in alveolar epithelial cells in RIPF needs to be further elucidated in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Independently of the precise mechanism affecting such non-canonical function of p53α, both fork stalling and dysregulated DDT pathway usage are known to cause genomic instability and thereby tumorigenesis [ 89 ]. Moreover, loss of fork protection and resulting DNA damage are known to be sufficient to induce EMT genes and thereby invasiveness and metastasis [ 157 ].…”
Section: The Role Of P53 Isoforms In Cancersmentioning
confidence: 99%